2007
DOI: 10.1111/j.1467-8535.2006.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Can mood‐inducing videos affect problem‐solving activities in a web‐based environment?

Abstract: The purpose of this study was to examine whether a video-induced positive and negative mood has a differential effect on subsequent problem-solving activities in a web-based environment. The study also examined whether task conditions (task demands) moderated the mood effect. As in traditional experimental mood-effect studies, the affective video materials were not related to the tasks. The results show that affective video clips did impact performance on an insight task but not on a divergent-thinking task. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Cyclothymic traits seem to be more beneficial to original thinking, as mixed emotional states entail the processing of a given task or situation as original or atypical. The occurrence of negative mood state also increases the motivation to redefine the problem and to find most common solutions to it unsatisfactory (Vosburg, 1998; Verleur, Verhagen & Heuvelman, 2007). Mixed emotional states may be conducive to creativity both in individual and in interpersonal settings.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclothymic traits seem to be more beneficial to original thinking, as mixed emotional states entail the processing of a given task or situation as original or atypical. The occurrence of negative mood state also increases the motivation to redefine the problem and to find most common solutions to it unsatisfactory (Vosburg, 1998; Verleur, Verhagen & Heuvelman, 2007). Mixed emotional states may be conducive to creativity both in individual and in interpersonal settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that video clips with various emotional purposes sensitise students and that this induction of feelings impacts on the resolution of tasks after exposure to the material (VERLEUR et al, 2007). Videos can explore clinical encounters, social situations or any relevant content or topics according to the proposed activity.…”
Section: Theory and Practice Of Critical Thinkingmentioning
confidence: 99%
“…They concluded that a bird documentary and a clip from When Harry Met Sally (WHMS) were the most powerful in producing neutral and positive moods, respectively. Verleur, Verhagen, and Heuvelman (2007) showed the clips to individuals through a computer and found them to be effective in inducing mood.…”
Section: Designmentioning
confidence: 99%